Factors Shaping Patients’ Engagement in Digital Health Self-Management Tools - Kaczmarek, Mateusz; Jenkins, Sarah; Al-Sabah, Reem (KMAN Counseling & Psychology Nexus, 2026)
This study aimed to identify and understand the factors that influence patients’ engagement with digital health self-management tools. This qualitative study used a phenomenological–interpretive design to explore patients’ lived experiences with digital self-management technologies. Twenty-one adult participants residing in Canada were recruited through purposive sampling. Data were collected using in-depth semi-structured interviews conducted via telephone or videoconferencing. Interviews were audio-recorded, transcribed verbatim, anonymized, and analyzed using thematic analysis supported by NVivo software. Coding proceeded iteratively until theoretical saturation was reached. Trustworthiness was strengthened through reflexive memoing, researcher triangulation, and detailed documentation of analytic procedures. Four overarching themes and multiple subthemes emerged from the data. Personal determinants—including health motivation, digital literacy, emotional responses, perceived usefulness, privacy boundaries, and lifestyle fit—significantly shaped engagement. Technology-related factors such as usability, interface clarity, personalization features, technical reliability, meaningful data visualization, interoperability, and perceived data security influenced tool adoption and sustained use. Healthcare system and provider influences—particularly provider endorsement, integration of digital data into consultations, and ongoing support—reinforced accountability and strengthened engagement. Social and contextual factors, including family encouragement, cultural attitudes, socioeconomic constraints, environmental infrastructure, competing life demands, and privacy expectations, further moderated participants’ engagement patterns. Collectively, the results indicate that engagement emerges from the interaction of individual, technological, clinical, and contextual dynamics rather than from any single factor. Patients’ engagement with digital health self-management tools is shaped by a complex interplay of personal motivations, technological design, provider involvement, and socio-environmental contexts. Findings highlight the need for user-centered, context-responsive, and clinically integrated digital solutions that address both individual preferences and broader structural realities.